AMALIYAH AL-ISTISYHAD (BOM BUNUH DIRI) DALAM TINJAUAN DAKWAH DAN HUKUM ISLAM - Busyro Busyro (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2010)
The struggle which is effort by our prophet Muhammad SAW and his companions for spreading out the Islamic religion is based on the missionary principle means using good manners. Many of obstacles faced by them as long as their efforts for build Islam for surely. Fortunately, they have been never giving their life up voluntarily to the enemies of Allah. In the history of Badar war, there was no an act of amaliyah al-istisyhad either to look for a win or to try intimidating their enemies. Unfortunately, as we know that in the recent, there is a phenomenon to popularize an act to sacrifice their life voluntarily to bombard their enemies. This act is done by them with the purpose that they will be a syuhada (death with the guarantee of paradise in hereafter) or getting amaliyah al-istisyhad. This act affects to the cynism of western view about Islamic religion, moreover they argue that Islamic religion is spread out by the uncivilized ways. From the study conducted showed that the act of self bomb has no strong of basic principle neither from Al-Qur’an nor As-sunnah. Moreover, this act is regarded as an act which is contradicted to the Islamic principle. However, this acts contributing for giving a negative effect and making part of Islamic religion into the low level of humanity.